Uncovering Islamic Job Happiness from Various Dimensions: A Study at Islamic Micro Finance Institution - Wijiharta Wijiharta; Salihah Khairawati; Nur Wening (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study aims to determine the assessment of employees of economic institutions with social nuances of KSSPS BMT on the dimensions of work happiness. This research uses quantitative methods. Thirty respondents selected the sample from 10 economic organizations with social and religious nuances KSSPS BMT (IMFI). Convenience data retrieval techniques. The data from the study were carried out with descriptive analysis. The assessment of the four work happiness dimensions (spiritual, psychological, social, and physical) reached a score of 4.28. The spiritual dimension received the highest assessment, while the physical dimension got the lowest assessment. Therefore, socially nuanced economic institutions managers need to pay more attention to the spiritual dimension of work happiness